1999
DOI: 10.1002/(sici)1521-3749(199910)625:10<1664::aid-zaac1664>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Crystal Structure of Cesium Nitratometalates(II), Cs2[M(NO3)4] (M = Mn, Co, Ni, Zn)

Abstract: Octahedral clusters from p‐block elements are rare; however, the only known molecular aggregate of this kind, [{(CO)5Cr}6Sn6]2−, has now been supplemented by the isoelectronic cluster [{(CO)5Cr}6Ge6]2− (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Unfortunately, these studies did not determine the exact geometry of [Co(NO 3 ) 4 ] 2− . Some other studies have reported tetranitratocobaltate(II) salts with various cations, and the crystal structures of these salts exhibited coordination numbers of 6, 35 7, 36‐38 and 8 36,37,39,40 . The difference in the coordination number of [Co(NO 3 ) 4 ] 2− is affected by the size and shape of the cations 35 …”
Section: Resultsmentioning
confidence: 94%
“…Unfortunately, these studies did not determine the exact geometry of [Co(NO 3 ) 4 ] 2− . Some other studies have reported tetranitratocobaltate(II) salts with various cations, and the crystal structures of these salts exhibited coordination numbers of 6, 35 7, 36‐38 and 8 36,37,39,40 . The difference in the coordination number of [Co(NO 3 ) 4 ] 2− is affected by the size and shape of the cations 35 …”
Section: Resultsmentioning
confidence: 94%